Mother Earth, Mother Africa World Religions and Environmental Imagination. - Chirongoma, Sophia (Mother Earth, Mother Africa Ser., 2022)
Ever since independence from Britain in 1966, Lesotho has been an experimental laboratory of various governance models. The country has experienced multi-party models, plain dictatorships, one-party dominated models, military juntas and, recently, coalition governments. The advent of coalition politics since 2012 has brought a paradigmatic shift in the entire socio-political landscape in the country.